Performance investigation of sliding vane expander based in-house development in a micro-scale ORC system - Wichean Singmai; Pichet Janpla; Kasemsil Onthong; Tongchana Thongtip; Kittiwoot Sutthivirode (Results in Engineering)
The expander plays a crucial role in the waste heat recovery to useful mechanical power via the ORC system. However, there is still a lack of a commercially available expander at a micro-scale ORC system. Therefore, the development of a sliding-vane expander operated in a micro-scale ORC system is proposed. The impact of the evaporator temperature and condensation temperature on the system performance is investigated by the ORC test rig. The evaporator temperature ranges from 65 to 85°C (heat source) and the condensation temperature (heat sink) ranges from 34 to 42°C. The working fluid used is R245fa. This work also proposes a mass flow model corrected by the volumetric efficiency, which is determined experimentally under different expansion pressure ratios and rotational speeds. The validation of the calculated results with another working fluid is implemented to indicate the accuracy of the model. It has been proven that the sliding-vane expander is workable under a wide range of operating conditions. A shaft power (useful mechanical work) of 108–182 W is found. For a certain working condition, the maximum shaft power is determined at a certain rotational speed. The thermal efficiency is around 0.85 - 1.6% depending on the working condition. The mass flow rate determined by the proposed model agrees well with the experiment even when the working fluid is changed (R141b used for validation). The error from predictions is around 12.0 – 15.6%. This work demonstrates the feasibility of the in-house developed expander in an ORC system, which may be an alternative way to be cost-effective for installing an ORC plant.